A Technical Note To the Eighth Plan of India (1992-97) - Planning Commission (Planning Commission, 1992)
Indian planning process is extremely complex. It involves outlining the strategies for development and the supporting policy environment, working out the macro-parameters for the growth and its sectoral pattern, allocation of resources between centre and states and for different sectoral activities, detailed allocation of budgetary support and consideration of specific projects/programmes and schemes in the public sector. Formalised modelling is used for working out the macro-parameters for growth and its sectoral pattern and allocation of resources for different sectoral activities. Since the Fifth Plan, the numerical exercises and the technical work at the back of the formulation of the plan are being presented separately in the form of a technical note. The technical note outlines the methodology of plan formulation in detail by capturing the diverse inter-relationships of forces and factors that lie behind the national plan and describe in detail the various assumptions, techniques and analysis that form the basis of the plan.
Government of India Planning Commission
Government Of India Planning Commission